2020
DOI: 10.21203/rs.3.rs-35331/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 T-cell epitopes define heterologous and COVID-19-induced T-cell recognition

Abstract: The SARS-CoV-2 pandemic calls for the rapid development of diagnostic, preventive, and therapeutic approaches. CD4+ and CD8+ T cell-mediated immunity is central for control of and protection from viral infections[1-3]. A prerequisite to characterize T-cell immunity, but also for the development of vaccines and immunotherapies, is the identification of the exact viral T-cell epitopes presented on human leukocyte antigens (HLA)[2-8]. This is the first work identifying and characterizing SARS-CoV-2-specific and c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 9 publications
10
41
0
Order By: Relevance
“…In line with other recent reports, we also observed in one unexposed donor very low frequencies of CD4 + and CD8 + T cells against spike and nucleocapsid proteins, respectively, probably due to cross-reactive cells primed against other SARS viruses [12][13][14]. We also used m24 Ab staining to con rm the induction of anti-vaccine CD4 + T cells after experimental immunization of a healthy volunteer with synthetic peptides from the spike and nucleocapsid proteins [9].…”
Section: Discussionsupporting
confidence: 90%
“…In line with other recent reports, we also observed in one unexposed donor very low frequencies of CD4 + and CD8 + T cells against spike and nucleocapsid proteins, respectively, probably due to cross-reactive cells primed against other SARS viruses [12][13][14]. We also used m24 Ab staining to con rm the induction of anti-vaccine CD4 + T cells after experimental immunization of a healthy volunteer with synthetic peptides from the spike and nucleocapsid proteins [9].…”
Section: Discussionsupporting
confidence: 90%
“…Results compiled from 8 experimental studies of T cell responses in a total of 1,259 convalescent COVID-19 patients (Le Bert et al, 2020;Chour et al, 2020;Peng et al, 2020;Nelde et al, 2020;Poran et al, 2020;Shomuradova et al, 2020;Ferretti et al, 2020;Snyder et al, 2020) revealed 303 unique T cell epitopes. Of these, 71 are CD8 + (HLA class I restricted), 21 are CD4 + (HLA class II restricted), while 211 epitopes had no HLA allele information reported ( Figure 1A).…”
Section: Sars-cov-2 T Cell Epitopes Identified By Studies Of Convalesmentioning
confidence: 99%
“…Data was compiled from 8 immunological studies (as of 7 August 2020) reporting SARS-CoV-2 T cell epitopes in convalescent COVID-19 patients. More specifically, epitope data was extracted from Figure 3 in (Chour et al, 2020), Table 1 in (Shomuradova et al, 2020), Extended Data Tables 2 and 3 in (Nelde et al, 2020), Figure 3 in (Poran et al, 2020), Table 1 in (Ferretti et al, 2020), Table 1 in (Le Bert et al, 2020), Tables 1 and 2 in (Peng et al, 2020), and data deposited by authors of (Snyder et al, 2020) in the Immune Epitope Database (IEDB).…”
Section: T Cell Epitope Data Derived From Convalescent Covid-19 Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is most likely that these individuals were previously infected with one of the four human coronaviruses (HCoV-229E, -NL63, -OC43 and -HKU1) that cause seasonal common cold. Nelde et al demonstrated evidence that the amino acid sequences of several SARS-CoV-2 T cell epitopes recognized by unexposed individuals are similar to some amino acid sequences in the four seasonal common cold human coronaviruses withidentities ranging from 10% to 89% (not 100% identity)(44). However, anyone has not shown evidence that people with this cross-reactivity are less susceptible to COVID-19.…”
mentioning
confidence: 99%